A Private, Nonprofit University's Experiences Designing a Competency-Based Degree for Adult Learners. Issue 1 (2nd January 2018) - McDonald, Nancy A.
Abstract: Competency-based higher education focuses on workplace competencies and often enables students to progress at their own pace. The university in this case study decided to pursue competency-based education (CBE) to offer working adults a convenient, self-paced way to earn a bachelor's degree. The mission of the university—to provide open access to career-oriented degrees for adults of all ages—drove many of the CBE decisions. However, after piloting the competency-based degree, the university found students were uninterested in an entirely self-paced program, so the institution incorporated self-paced mini courses into its traditional degree. This case study examines how external regulations, as well as internal economics and policies, influenced the CBE program's design. The purpose of this research was to understand the key design decisions, so others may learn from the findings. The innovative, self-paced approaches that evolved from this study may interest other institutions serving adult students.